Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Song Trần

Tính giá trị biểu thức:

7) G= \(\frac{1}{25}-\frac{4}{27}+\left(\frac{-23}{27}+\frac{-1}{25}-\frac{5}{43}\right)+\frac{5}{43}-\frac{4}{7}\)

Trang Nhung
23 tháng 7 2016 lúc 10:40

\(G=\frac{1}{25}-\frac{4}{27}+\left(\frac{-23}{27}+\frac{-1}{25}-\frac{5}{43}\right)+\frac{5}{43}-\frac{4}{7}\)

\(=\frac{1}{25}-\frac{4}{27}+\frac{-23}{27}+\frac{-1}{25}-\frac{5}{43}+\frac{5}{43}-\frac{4}{7}\)

\(=\left(\frac{1}{25}+\frac{-1}{25}\right)+\left(\frac{-4}{27}+\frac{-23}{27}\right)+\left(\frac{-5}{43}+\frac{5}{43}\right)-\frac{4}{7}\)

\(=0+\left(-1\right)+0-\frac{4}{7}\)

\(=\frac{-11}{7}\)

Nguyễn Mạnh Tân
23 tháng 7 2016 lúc 10:30

-11phần7

soyeon_Tiểu bàng giải
23 tháng 7 2016 lúc 10:32

\(G=\frac{1}{25}-\frac{4}{27}+\left(\frac{-23}{27}+\frac{-1}{25}-\frac{5}{43}\right)+\frac{5}{43}-\frac{4}{7}\)

\(G=\frac{1}{25}+\frac{-4}{27}+\frac{-23}{27}+\frac{-1}{25}+\frac{-5}{43}+\frac{5}{43}+\frac{-4}{7}\)

\(G=\left(\frac{1}{25}+\frac{-1}{25}\right)+\left(\frac{-4}{27}+\frac{-23}{27}\right)+\left(\frac{-5}{43}+\frac{5}{43}\right)+\frac{-4}{7}\)

\(G=0+\left(-1\right)+0+\frac{-4}{7}\)

\(G=-1+\frac{-4}{7}\)

\(G=\frac{-7}{7}+\frac{-4}{7}=\frac{-11}{7}\)


Các câu hỏi tương tự
Nguyễn Châu Mỹ Linh
Xem chi tiết
nguyễn thị lan trinh
Xem chi tiết
nguyễn thị lan trinh
Xem chi tiết
Song Trần
Xem chi tiết
Hoàng Đình Vinh
Xem chi tiết
Đỗ Thanh Huyền
Xem chi tiết
nguyễn ngọc minh hà
Xem chi tiết
Phan Thị Xuân Uyên
Xem chi tiết
ICHIGO HOSHIMIYA
Xem chi tiết